Phylogenomics corroborates morphology: New discussions on the systematics of Trichostomatia (Ciliophora, Litostomatea) - Cedrola, Franciane; Gürelli, Gözde; Vinicius Xavier Senra, Marcus; Jasmine Arminini Morales, Millke; Júnio Pedroso Dias, Roberto; Nisaka Solferini, Vera (Elsevier BV, 2024)
The subclass Trichostomatia (Ciliophora, Litostomatea) constitutes a well-supported monophyletic group, which includes ciliates exclusively found as symbionts of vertebrates, primarily herbivorous mammals. Recent molecular analyses reinforce the subclass monophyly, though almost all orders, suborders, families, and genera are found to be non-monophyletic. Here, we reconstructed the evolutionary history of the subclass Trichostomatia using a phylogenomic approach and discussed some systematic inconsistencies. We propose a new Ophryoscolecidae genus, Dagostonium, to include Diplodinium polygonale. Monoposthium cynodontum is transferred to the genus Cycloposthium.
Keywords: Species Specificity; Ciliophora; Genome, Protozoan; Phylogeny